The Effect of Problem-Based Learning and Discovery Learning Models on Student Learning Outcomes Based on Teacher's TPACK - Nofitri, Tya Wahyu; Octoria, Dini (Economic Education Analysis Journal, 2024)
Learning outcomes are a reflection of students' understanding of the material delivered by the teacher. Teachers' success in teaching can be measured from the learning outcomes achieved by students. This study aims to determine the effect of the problem-based learning model, discovery learning, and Technological Pedagogical Content Knowledge (TPACK) of teachers on the learning outcomes of grade X students in Economics subjects. This research is quantitative research with an experimental method. The sample in this study were students of class X.E-9 and X.E-10 SMA Negeri 2 Surakarta in the academic year 2023/2024 who were taken by purposive sampling technique with the provision of the class with the lowest average score in economics. The data collection technique used observation for the learning model, tests to measure student learning outcomes, and questionnaires to measure teachers' TPACK levels. Research data analysis techniques used were descriptive statistical analysis and Anova Two-way. The results show that the problem-based learning model, discovery learning, and teacher TPACK level have been proven to affect student learning outcomes in Economics subjects. The problem-based learning model proved to be better when compared to the discovery learning model, because the average score of Economics learning outcomes of students taught using the problem-based learning model was higher than the average score of Economics learning outcomes of students taught using the discovery learning model. However, both learning models are equally good when combined with high teacher TPACK levels. Because, students with high teacher TPACK get better learning outcomes compared to students with medium and low teacher TPACK.